2009
DOI: 10.1637/8456-082208-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Two Distinct Bursal B-Cell Subpopulations Following Infectious Bursal Disease Virus Infection of White Leghorn Chickens

Abstract: Infectious bursal disease virus (IBDV) is an immunosuppressive virus which primarily infects IgM B-cells in the bursa of Fabricius. Flow cytometric analysis was used to phenotype B-cell populations in the bursa and spleen following IBDV infection. In the bursa, two IgM B-cell subpopulations, designated as A and B, were identified based on cell size and granularity. While both subpopulations differentially expressed IgM and Bu-1b surface markers, both groups displayed major histocompatibility complex class II s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Furthermore, a high correlation coefficient between the NDV-HI titer and the number of normal follicles was found in the wild-type group. These results suggested that the retained number of normal follicles is important for immunoreactivity in chickens infected with IBDV, in addition to a previously reported factor, namely the extent of depletion of lymphocytes in the BF [ 10 , 19 , 26 ].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, a high correlation coefficient between the NDV-HI titer and the number of normal follicles was found in the wild-type group. These results suggested that the retained number of normal follicles is important for immunoreactivity in chickens infected with IBDV, in addition to a previously reported factor, namely the extent of depletion of lymphocytes in the BF [ 10 , 19 , 26 ].…”
Section: Discussionsupporting
confidence: 50%
“…The immunosuppression of IBD is known to be caused by the depletion of lymphocytes in the bursa of Fabricius (BF) [ 10 , 19 , 26 ], which results in macroscopic BF atrophy, the most characteristic lesion of IBD [ 12 ]. Live vaccine strains of IBDV also cause BF atrophy to various extents [ 17 , 21 ].…”
mentioning
confidence: 99%
“…But older studies suggested that IBDV may target receptors mainly presented on the surface of IgM-bearing cells. vvIBDV-exposure did not reduce the levels of total serum IgA, IgG, and IgM, nor did it affect IgG and IgA B-cells in the spleen, while the caecum was not investigated [ 52 ]. Therefore, we speculate that the decrease in IgM+ B cells in the BF and CT possibly led to the subsequent reduction of IgA+ secreting cells in the caecum.…”
Section: Discussionmentioning
confidence: 99%
“…Given the demonstration by Petkov et al [24] that a Bu-1-F + and IgM + subpopulation in the bursa is targeted in IBDV infections, the potential of the present agglomerate system for study of NDV infection was examined. The presence of NDV particles clustered in the agglomerate after 24 hours is consistent with productive infection and the location of viral particles within disrupted mitochondria resembles that observed following infection of chick cells with reticuloendotheliosis virus [25].…”
Section: Discussionmentioning
confidence: 99%